2020
DOI: 10.1080/13696998.2020.1717499
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cladribine tablets versus fingolimod in patients with highly active relapsing multiple sclerosis in Portugal

Abstract: Aims: To assess the cost-utility of cladribine tablets versus fingolimod in patients with highly active relapsing-remitting multiple sclerosis (RRMS) in Portugal. Methods: A 1-year cycle cohort-based Markov state transition model was developed to simulate disease progression, measured by Kurtzke Expanded Disability Status Scale (EDSS), relapses, and conversion to secondary-progressive MS (SPMS). Patients were assumed to remain on treatment until progression to EDSS level 7, conversion to SPMS, or complete loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results also showed that doing sensitivity analysis did not change the status of rituximab as the most effective drug regimen, suggesting the robust study results. In this regard, the present study is in line with those of Rezaei et al (2019) and Taheri et al (2019) in the country, and Walter et al (2018), Hettle et al (2018), and Montgomery et al (2017) abroad [ 37 , 61 , 62 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results also showed that doing sensitivity analysis did not change the status of rituximab as the most effective drug regimen, suggesting the robust study results. In this regard, the present study is in line with those of Rezaei et al (2019) and Taheri et al (2019) in the country, and Walter et al (2018), Hettle et al (2018), and Montgomery et al (2017) abroad [ 37 , 61 , 62 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…Montgomery et al [ 73 ] in the UK examined the cost-effectiveness of fingolimod and natalizumab and found that the cost of the former was £ 334,897.93 and its obtained QALY was 6.18. However, the cost and QALY of the latter were £ 337,501.15 and 6.35, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1 Flow chart of the study selection process using a 31-health-state Markov model [43], one study conducted CEA using a 5-year cohort-based Markov model [44], one study conducted CEA using a 1-year cycle cohort-based Markov state transition model [45], one study conducted CEA using a lifetime Markov model [46], five studies conducted CEA [2,[47][48][49][50], two studies conducted both CEA and CBA [10,51], one study conducted CEA using simulation model [52], one study conducted CEA using a treatment-sequence model [53], one study conducted CUA and budget impact analysis (BIA) using a Markov state transition model [54], one study conducted CEA using a published Markov structure with health states based on the Expanded Disability Status Scale (EDSS) [55], one study conducted CEA using a Markov state transition model [56], one study conducted CEA using a Markov economic model [57], five studies conducted CEA using a cohort Markov economic model [10,13,17,51,58], one study conducted CEA using a microsimulation model [19], one study conducted CEA using a discrete-time Markov model [59], one study condcuted CEA using a cohort-based multi-state Markov model [60], and one study conducted CEA using a probabilistic Markov model (second-order Monte Carlo simulation) [61] (Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study was conducted from the UK societal cost perspective [22], two from UK National Health Service [2,58], one from UK third-party payer perspective [55], two from Canadian healthcare system perspective [13,59], one from Chilean health care public sector perspective [38], one from Kingdom of Saudi Arabia payer's perspective [56], two from Payer perspective [34,45], one from the Colombian healthcare system perspective [57], one from Italian societal perspective [28], one from Italian National Healthcare System perspective [60], one study from Swiss health insurance perspective [30], one from Payer and societal perspective [17], eleven studies from societal perspective [19, 27, 29, 31-33, 35, 42-44, 51], three studies from Ministry of Health perspective [50,52,64], one from Third-party payer perspective [23], one from Saudi payer perspective [24], two from US payer perspective [18,37], one from US health care payer perspective [47], one from both National Health Service and Personal Social Services perspective [25], two from Spanish National Health System [39,61], one from thirdparty payer perspective [63], one from both patients and third-party payers perspective [26], one from healthcare perspective [36], one from public healthcare perspective [49], one from both National Health Service and Personal Social Services perspective [41], one from both thirdparty payer & Societal [46], and one from Finnish payer perspective and Scenario analysis with a societal perspective [10], one from both health economics and societal perspective…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A simulation model assessing the efficiency of cladribine tablets or DMTs delivered by infusion from a facility perspective in the UK found that cladribine tablets could decrease the burden of hospital-based administration and monitoring [ 78 ]. However, the cost of DMTs is an important driver in many cost-assessment models, and cladribine tablets has been found to be cost effective compared to alternative treatments in modeling based on use in many country-specific settings, including Finland [ 79 ], Portugal [ 80 ], Spain [ 81 ], Saudi Arabia [ 82 ], Chile [ 83 ], Iran [ 84 ], and Poland [ 85 ].…”
Section: Emerging Data On the Efficacy Of Cladribine Tabletsmentioning
confidence: 99%